Arabic Calligraphy in the Ornamentation of Architecture and Ottoman Arts - LAMOUDI , TIDJANI (The Algerian Historical Journal, 2026)
The abundant material and archaeological evidence characterizing Ottoman art across much of the regions once under Ottoman rule testifies to the grandeur of the empire, particularly in architecture and, more broadly, in its cultural achievements. Visitors to these monuments cannot help but sense the significance of Ottoman contributions to urban development and civilization. Among the most distinctive features of Ottoman heritage are the decorative arts that adorn these structures, with calligraphic panels holding a prominent place. This article aims to shed light on the art of “painting with words” and the use of Arabic calligraphy as a decorative element in Ottoman art, showing the Ottomans’ reverence for the Arabic script and their respect for its close connection with the Islamic faith.